2019
DOI: 10.17576/jkmjc-2019-3502-29
|View full text |Cite
|
Sign up to set email alerts
|

Parental Awareness on Cyber Threats Using Social Media

Abstract: In recent years, the use of Internet has increased exponentially and most of the users are from adolescents. Internet technology has facilitated cyber threats activities and many of the cases are from adolescents. Users at this age need parental guidance and support because they are still naïve or immature to understand the risks of Internet. Hence, many developed countries have imposed on clear guidelines on the Internet to control and guide the users and understand the risks they will encounter when they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 5 publications
2
17
0
1
Order By: Relevance
“…The current study's findings suggest that parents may be less likely to underestimate cyber victimization. This may be because of an overall parental awareness that online threats are an increasing issue (Ahmad et al, 2019). Recent research has shown that parents of children and adolescents are beginning to inform themselves about cyber safety and protecting their child, and this might include setting rules, discussing with other parents or attending talks (Ahmad et al, 2019).…”
Section: No Restrictive Mediationmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study's findings suggest that parents may be less likely to underestimate cyber victimization. This may be because of an overall parental awareness that online threats are an increasing issue (Ahmad et al, 2019). Recent research has shown that parents of children and adolescents are beginning to inform themselves about cyber safety and protecting their child, and this might include setting rules, discussing with other parents or attending talks (Ahmad et al, 2019).…”
Section: No Restrictive Mediationmentioning
confidence: 99%
“…This is related to the fact that today's youth are exposed to technology earlier than their parents were, giving them more time to become experts at using it (Wong, 2010). This gap in skills makes it difficult for parents to teach and guide their child on how to identify threating and reliable information online (e.g., a photoshopped picture; Ahmad et al, 2019;Livingstone & Bober, 2004). Although research has shown that digital media usage increases with age, it is now reported to be accessed by elementary school children (Mascheroni & Cuman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Privacy is another key challenge. Social media platforms are designed for open communication and sharing, which can inadvertently expose learners' personal information (Ahmad et al, 2019). In an educational context, where privacy and data protection are paramount, educators and institutions need to educate learners about privacy settings, data security, and responsible sharing.…”
Section: Challenges and Solutions In Sm-oers Implementation Processmentioning
confidence: 99%
“…Parental awareness differs from country to country and depends on the level of knowledge of parents about internet use. For example, a recent Malaysian study found that parental awareness of cyber threats still needs to be improved to promote cyber safety [ 37 ]. In many cases, Malaysian parents were unaware of their children’s unregulated access and exposure to inappropriate online sites, subjecting them to cyber threats.…”
Section: Literature Reviewmentioning
confidence: 99%